The Application Video Media for Increase Motivation and Results Study Student on Material Human Life Needs - Zarkasih (Journal of General Education Science, 2024)
This research aims to increase student motivation in the Community Economics learning process regarding the Needs of Human Life in class VII students of SMP Negeri 2 Pasir Limau Kapas Semester I of the 2023/2024 academic year. This research was conducted because of student motivation in learning Community Economics about the Needs of Human Life in class VII students of SMP Negeri 2 Pasir Limau Kapas Semester I of the 2023/2024 academic year. still relatively lacking. The research subjects were 20 students in class VII of SMP Negeri 2 Pasir Limau Kapas Semester I of the 2023/2024 academic year. The procedures for carrying out actions and implementation at the research location are divided into 2 cycles. Each cycle consists of four stages, namely: planning, acting, observing and reflecting and is carried out in 4 meetings. Data collection techniques use tests, observations, and documentation of learning activities. Analysis is carried out using techniques data analysis qualitative And technique analysis data qualitative. Results this research shows that the use of the PBL learning model with image media in learning Community Economics about the Needs of Life for Humans and Capabilities improve skills students in making lapbooks of material needed for human life in class VII SMP N 2 Pasir Limau Kapas Semester I Academic Year 2023/2024.